Consumer Marketing Strategy and E-Commerce in the Last Decade: A Literature Review - Rosário, Albérico; Raimundo, Ricardo (Journal of theoretical and applied electronic commerce research, 2021)
E-commerce is deemed as the sale and purchase of goods and services through the internet in exchange for money and data transfer to complete the transactions. E-commerce is at the forefront of transforming marketing strategies, based on new technologies, and facilitates product information and improved decision-making. In this way, marketing strategy increasingly require large amounts of information to better understand client needs, which raises the question of choosing the right marketing strategy to better fit consumer expectations. This literature review aims to shed light on both the recent growth of e-commerce literature and its interplay with consumer marketing strategy. Extant research has examined this change in human interaction due to social network building, mostly through the themes of online marketing and social media marketing, also comprehending issues such as cost efficiency, information quality and trust development towards online shopping. Nevertheless, existing research has not shown in full all the research streams, how they interact with each other and its potential knowledge development. Thus, a literature review on consumer marketing strategy for e-commerce in the last decade is opportune. This paper aims to identify research trends in the field through a Systematic Bibliometric Literature Review (LRSB) of research on marketing strategy for e-commerce. The review includes 66 articles published in the Scopus® database, presenting up-to-date knowledge on the topic. The LRSB results were synthesized across current research subthemes. The following findings are presented: Amidst the current competitive global business environment, companies tend to respond with strategies for e-commerce and online businesses that resort to e-commerce platforms and social networking to better understand consumer needs, facilitate consumer marketing strategy and share innovative information. The originality of the paper relies on its LRSB method, together with extant review of articles that have not been categorized so far.